Landslides - Zhang, Yuanzhi; Cheng, Qiuming (IntechOpen, 2022)
In recent years, landslides and their impacts have drawn increasing awareness globally, regionally, and locally. Landslides as catastrophic events can cause human injury, loss of life, and economic devastation as well as destroy infrastructures and cultural and natural heritage. New technologies, including interferometric synthetic aperture radar (InSAR) and geographic information systems (GIS), are being thoroughly adopted and applied to dynamic and process monitoring and modelling of coal mine and marine landslides, land subsidence, and tsunami landslides. These technologies are also being used for hazard mapping and assessment, early warning and evacuation, and regional or local landslide mitigation. This book discusses these topics and more.